Nutritional intake and anthropometric characteristics are associated with endurance performance and markers of low energy availability in young female cross-country skiers - Oona Kettunen; Ritva Mikkonen; Vesa Linnamo; Jaakko Mursu; Heikki Kyröläinen; Johanna K. Ihalainen (Taylor & Francis Group, 2023)
Background Low energy availability (LEA) can have negative performance consequences, but the relationships between LEA and performance are poorly understood especially in field conditions. In addition, little is known about the contribution of macronutrients to long-term performance. Therefore, the aim of this study was to evaluate if energy availability (EA) and macronutrient intake in a field-based situation were associated with laboratory-measured performance, anthropometric characteristics, blood markers, training volume, and/or questionnaire-assessed risk of LEA in young female cross-country (XC) skiers. In addition, the study aimed to clarify which factors explained performance. Methods During a one-year observational study, 23 highly trained female XC skiers and biathletes (age 17.1 ± 1.0 years) completed 3-day food and training logs on four occasions (September-October, February-March, April-May, July-August). Mean (±SD) EA and macronutrient intake from these 12 days were calculated to describe yearly overall practices. Laboratory measurements (body composition with bioimpedance, blood hormone concentrations, maximal oxygen uptake (VO2max), oxygen uptake (VO2) at 4 mmol·L−1 lactate threshold (OBLA), double poling (DP) performance (time to exhaustion), counter movement jump (height) and the Low Energy Availability in Females Questionnaire (LEAF-Q)) were completed at the beginning (August 2020, M1) and end of the study (August 2021, M2). Annual training volume between measurements was recorded using an online training diary. Results The 12-day mean EA (37.4 ± 9.1 kcal·kg FFM−1·d−1) and carbohydrate (CHO) intake (4.8 ± 0.8 g·kg−1·d−1) were suboptimal while intake of protein (1.8 ± 0.3 g·kg−1·d−1) and fat (31 ± 4 E%) were within recommended ranges. Lower EA and CHO intake were associated with a higher LEAF-Q score (r  = 0.44, p  = 0.042; r  = 0.47, p  = 0.026). Higher CHO and protein intake were associated with higher VO2max (r  = 0.61, p  = 0.005; r  = 0.54, p  = 0.014), VO2 at OBLA (r  = 0.63, p  = 0.003; r  = 0.62, p  = 0.003), and DP performance at M2 (r  = 0.42, p  = 0.051; r  = 0.44, p  = 0.039). Body fat percentage (F%) was negatively associated with CHO and protein intake (r = -0.50, p  = 0.017; r = -0.66, p  = 0.001). Better DP performance at M2 was explained by higher training volume (R2  = 0.24, p  = 0.033) and higher relative VO2max and VO2 at OBLA at M2 by lower F% (R2  = 0.44, p  = 0.004; R2  = 0.47, p  = 0.003). Increase from M1 to M2 in DP performance was explained by a decrease in F% (R2  = 0.25, p  = 0.029). Conclusions F%, and training volume were the most important factors explaining performance in young female XC skiers. Notably, lower F% was associated with higher macronutrient intake, suggesting that restricting nutritional intake may not be a good strategy to modify body composition in young female athletes. In addition, lower overall CHO intake and EA increased risk of LEA determined by LEAF-Q. These findings highlight the importance of adequate nutritional intake to support performance and overall health.